Determinan Dan Ketimpangan Sosial Ekonomi Pernikahan Dini Pada Kalangan Wanita Di Kabupaten Magelang - Ayu Rofi Widayanti; Poeja Pramudianti; Zenia Tata Rahayu; Afina Khusna Mufidah; 5Retnosari, S,Pd., M.Si. (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Indonesia is ranked 37th in the country with the highest rate of early marriage in the world, and is ranked second in ASEAN. Meanwhile, Central Java Province is ranked 23rd out of 33 provinces in Indonesia. The percentage of early marriage among women in Magelang Regency is 22% (BPS, 2017). The aim of this research is to analyze the determinant factors that influence the socio-economic gap in early marriage in Magelang Regency. This research uses observation methods and interview methods. The research sample will be carried out in Pakis District with the highest number of marriage dispensation requests, 20 cases. The data obtained by the researcher through observations and interviews was then compiled, summarized and outlined in a complete report description which was then prepared systematically and in detail regarding the research object. The results of this research are a phenomenon that occurs within a simple scope in Magelang Regency from year to year there is an increase in requests for marriage dispensation. Cases of requests for marriage dispensation in 2018 – 2020 in Magelang Regency are still increasing, marriages occur at an early age, even before the permitted age and readiness for marriage. This increase is in line with the increase in the poverty line that occurred in Magelang Regency from 2018 - 2020. Judging from the number of poor people who experienced a quite drastic increase in 2020, that year there was an increase in cases of requests for assistance. marriage dispensation which jumped to 533 cases. It is hoped that this research can increase public knowledge regarding the determining factors of early marriage so that they can avoid or minimize early marriage.